Tinjauan Singkat Perkembangan Animasi Indonesia dalam Konteks Animasi Dunia - Arik Kurnianto (Bina Nusantara University, 2015)
The purpose of this study was to assess the development of animated films in Indonesia based on historical studies to determine simultaneously mapping the history Indonesia in the context of world/global animation history. This study also examines the relationship between the histories of Indonesiananimated films with history first entry of the film in Indonesia which began the Dutch colonial era. According to Stephen Cavalier, the world history of animation was divided into five large round starts from the era before 1900 (The Origin of Animation) to the digital era (1986-2010). Based results of the study, Indonesian animation in the context of five major round of world animation, though have long been in contact with foreign-made films and animation (Disney Studio) has into Indonesia from the early 20th century (the early 1900s), the animation is produced Indonesia has only emerged in the '50s through the vision of a Soekarno, the first President. 1950 in the world of animation history entered the era of transition from gold age of traditional animation/cartoon (golden age of cartoons) are dominated by studio Disney to the era of television (television era). In a review of the history of animation, the era of the '50s travel half a century is the era of the modern world of animation history. Based on the facts the Indonesian animation has actually grown quite long, but the development of animation in Indonesia was very slow when seen in the context of the world animation history.